Challenges and impacts of religious endowments on global economics and finance - Buerhan Saiti; Sarea, Adel M. (Business Science Reference, 2019)
« Poverty is one of the top problems the Muslim community faces today. A scholastic approach towards a solution based on the values and cultural contexts of the Muslim community holds great importance and significance to the Islamic civilizations and modern economic and cultural applications in the world. 'Challenges and Impacts of Religious Endowments on Global Economics and Finance' is a pivotal reference source that examines the role of waqf and similar endowments in Islamic financial systems and how these religious endowments impact global economics and finance. While highlighting topics such as Islamic finance, risk management, and economic development, this publication explores adopting Islamic approaches to contemporary socio-economic issues and the methods of content analysis and meta-analysis methods. This book is ideally designed for professionals, economist regulators, financial analysts, academics, researchers, and postgraduate students seeking current research on modernized Islamic economic models in order to tackle the problem of fiscal deficiency. « (Verlagsbeschreibung)